2020
DOI: 10.1186/s13643-020-01483-7
|View full text |Cite
|
Sign up to set email alerts
|

Identifying, describing, and assessing interventions that support new graduate nurse transition into critical care nursing practice: a systematic review protocol

Abstract: Background Given a persistent nursing shortage in Canada and a decline in new nurses entering the profession, new graduate nurses (NGNs) are being hired into positions historically reserved for more experienced staff. Critical care settings, which are areas of specialty nursing practice, are now routinely hiring NGNs in many hospitals. While evidence on NGN transition into critical care is emerging, best practices around training and support for these nurses are limited internationally, and non-existent within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Additionally, we hypothesized that being a new nurse with less years of experience at bedside would translate to greater job satisfaction because of fewer opportunities and time for burnout to occur. However, the data limited us to 5 years or less in defining new nurse status, where current literature shows burnout (resulting in high turnover rates) occurring as quickly as 1–2 years (Vanderspank-Wright et al, 2020). To that end, studies have demonstrated that nurses’ decision to leave the workforce is associated with low job satisfaction (Aiken et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we hypothesized that being a new nurse with less years of experience at bedside would translate to greater job satisfaction because of fewer opportunities and time for burnout to occur. However, the data limited us to 5 years or less in defining new nurse status, where current literature shows burnout (resulting in high turnover rates) occurring as quickly as 1–2 years (Vanderspank-Wright et al, 2020). To that end, studies have demonstrated that nurses’ decision to leave the workforce is associated with low job satisfaction (Aiken et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…NGNs in the critical care setting face a variety of unique factors that can make the transition to practice especially challenging. Success in the critical care environment requires in-depth knowledge and specialized training in a fast-paced, clinically complex, and technologically advanced setting (Vanderspank-Wright et al, 2020). Administration and titration of sedation, vasopressors, vasodilators, and inotropic agents are common, requiring consideration of individual hemodynamic responses, avoidance of adverse effects, and patient instability (Mikula, 2019).…”
Section: Introductionmentioning
confidence: 99%